Triggered high-mass star formation in the H ii region W 28 A2: A cloud–cloud collision scenario. (13th June 2020) - Hayashi, Katsuhiro; Yoshiike, Satoshi; Enokiya, Rei; Fujita, Shinji; Yamada, Rin; Sano, Hidetoshi; Torii, Kazufumi; Kohno, Mikito; Nishimura, Atsushi; Ohama, Akio; Yamamoto, Hiroaki; Tachihara, Kengo; et al.
Abstract: We report on a study of the high-mass star formation in the H ii region W 28 A2 by investigating the molecular clouds that extend over ∼5–10 pc from the exciting stars using the 12 CO and 13 CO ( J = 1–0) and 12 CO ( J = 2–1) data taken by NANTEN2 and Mopra observations. These molecular clouds consist of three velocity components with CO intensity peaks at V LSR ∼ −4 km s −1, 9 km s −1, and 16 km s −1 . The highest CO intensity is detected at V LSR ∼ 9 km s −1, where the high-mass stars with spectral types O6.5–B0.5 are embedded. We found bridging features connecting these clouds toward the directions of the exciting sources. Comparisons of the gas distributions with the radio continuum emission and 8 μm infrared emission show spatial coincidence/anti-coincidence, suggesting physical associations between the gas and the exciting sources. The 12 CO J = 2–1 to 1–0 intensity ratio shows a high value (≳0.8) toward the exciting sources for the −4 km s −1 and +9 km s −1 clouds, possibly due to heating by the high-mass stars, whereas the intensity ratio at the CO intensity peak ( V LSR ∼ 9 km s −1 ) decreases to ∼0.6, suggesting self absorption by the dense gas in the near side of the +9 km s −1 cloud. We found partly complementary gas distributions between the −4 km s −1 and +9 km s −1 clouds, and the −4 km s −1 and +16 km s −1 clouds. The exciting sources are located toward the overlapping region in the −4 km s −1 and +9 km s −1 clouds. Similar gas properties are found in the Galactic massive star clusters RCW 38 and NGC 6334, where an early stage of cloud collision to trigger the star formation is suggested. Based on these results, we discuss the possibility of the formation of high-mass stars in the W 28 A2 region being triggered by cloud–cloud collision.